IMPLEMENTASI PENEGAKAN HUKUM TINDAK PIDANA KORUPSI Di LEMBAGA PEMASYARAKATAN SUKAMISKIN - Nadilla Arisandi (2021)
A crime is an offense committed by a person intentionally or unintentionally. Criminal acts can occur anywhere without exception within the Correctional Institution. Criminal acts within the Correctional Institution that we often hear about are criminal acts of corruption such as bribery and gratuities. This makes the image of the Correctional Institution bad in the eyes of the public. The purpose of this study is to determine the forms and factors that cause corruption in the Sukamiskin Correctional Institution and how to implement the law enforcement of corruption in the Sukamiskin Correctional Institution. The author uses the type of juridical normative and empirical juridical research. Normative juridical research is obtained from literature studies by citing literature books, previous journals and statutory regulations. While empirical juridical research is research that has an object of study on community behavior. The behavior of the people studied is the behavior that arises as a result of interacting with the existing norm system. The conclusion of this study is that there are several factors that influence inmates to take bribes and gratuities such as wanting to have luxurious facilities and correctional employees who want additional income. This is not in accordance with the correctional procedures described and regulated in the Regulation of the Minister of Law and Human Rights Number 6 of 2013.